ІСТОРИЧНІ АСПЕКТИ СТАНОВЛЕННЯ ТА РОЗВИТКУ КРИМІНАЛЬНОЇ ВІДПОВІДАЛЬНОСТІ ЗА ПОГРОЗУ АБО НАСИЛЬСТВО ЩОДО ЖУРНАЛІСТА - Бондарчук, Анна Сергіївна (SUPREMANCE OF LAW, 2019)
The article deals with the general tendencies of the formation and development of criminal liability for the violation of the legal professional activity of journalists and persons engaged in publishing activities that took place at different stages of state and law theories development in Ukraine. The theoretical and legal aspects of the consolidation of such liability in the legislation that acted on the lands of modern Ukraine and author’s own approaches to the periodization of the development of criminal liability for threats or violence against a journalist.